Affinity capillary electrophoresis and density functional theory employed for the characterization of hexaarylbenzene-based receptor complexation with alkali metal ions - Ehala, Sille; Toman, Petr; Rathore, Rajendra; Makrlík, Emanuel; Kašička, Václav (Electrophoresis, 2011)
In this study, affinity capillary electrophoresis (ACE) and quantum mechanical density functional theory (DFT) calculations were combined to investigate non-covalent binding interactions between the hexaarylbenzene-based receptor (R) and alkali metal ions, Rb(+) and Cs(+) , in methanol. The apparent binding (stability) constants (K(b) ) of the complexes of receptor R with alkali metal ions in the methanolic medium were determined by ACE from the dependence of effective electrophoretic mobility of the receptor R on the concentration of Rb(+) and Cs(+) ions in the BGE using a non-linear regression analysis. The receptor R formed relatively strong complexes both with rubidium (log K(b) =4.04±0.21) and cesium ions (log K(b) =3.72±0.22). The structural characteristics of the above alkali metal ion complexes with the receptor R were described by ab initio density functional theory calculations. These calculations have shown that the studied cations bind to the receptor R because they synergistically interact with the polar ethereal fence and with the central benzene ring via cation-π interaction.
Keywords: Electrophoresis, Capillary; elektroforéza kapilární; Models, Molecular; methanol; Regression Analysis; rubidium; Cesium; benzenové deriváty; Rubidium; Benzene Derivatives; Methanol; Nonlinear Dynamics; molekulární modely; regresní analýza; nelineární dynamika; cesium